Efficacy of 4% chlorhexidine in preventing neonatal umbilical cord infection (Journal of Fatima Jinnah Medical University, 2020)
Background: Umbilical cord stump is a budding point for bacterial colonization subsequently leading to sepsis that contributes to high neonatal morbidity and mortality, if not properly managed. Antiseptic care can significantly reduce omphalitis and ultimately improve newborn survival. Objective of this study was to see the efficacy of 4% chlorhexidine use to prevent umbilical cord infection in neonates.Subjects and methods: It was a comparative analytical study conducted in Neonatal unit, Sir Ganga Ram Hospital (SGRH) Lahore from July, 2016 till January, 2017. One hundred neonates were enrolled and randomized into two equal group by simple random method (50 each). In one group, nothing was applied to cord while in chlorhexidine group, 4% chlorhexidine gel was applied on umbilicus and around it, once daily for 7 days or till cord detached whichever came early. First application was done by a nurse followed by duly trained mother/caregiver. The signs of omphalitis (redness, pus or localized oedema) were observed and recorded for each neonate in both groups. Chi square test was used to see the difference in omphalitis in these groups with p˂ 0.05 considered as statistically significant result.Results: Out of 100 neonates, 29 (58%) and 23 (46%) males while 21 (42%) and 27 (54%) females neonates belonged to dry care and chlorhexidine group respectively. Nineteen (38%) neonates with dry cord had omphalitis compared to only 5 (10%) in chlorhexidine group (p 0.001). Neonates with chlorhexidine application showed prolonged mean cord separation time (7.9±1.5 days) compared to dry care (6.1±1.8 days). Conclusion: The use of 4% Chlorhexidine was effective to lower omphalitis compared to neonates with dry cord care.
Keywords: Umbilical cord; Chlorhexidine; Dry cord; Omphalitis; Prevention